The psychosocial impact of madrasah infrastructure: A qualitative evaluation of BAZNAS philanthropic program - Hadid, Marwan; Al-Wathani, M. Saddam Kiramuddin Al-Wathani; Sahipudin, Sahipudin (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2026)
This study investigates the intersection of Islamic philanthropy and educational psychology by evaluating the "Madrasah Layak Belajar" (MLB) program by BAZNAS RI. While infrastructure is often viewed through a technical lens, this research conceptualizes it as a psychosocial intervention. Using a qualitative case study at MI Al-Muslimun NW, data were gathered through semi-structured interviews and observations. Findings suggest that improved physical facilities such as lighting, ventilation, and furniture act as a catalyst for emotional readiness and student motivation. The physical environment functions as a "third teacher," where structural upgrades reduce cognitive load and foster a sense of institutional dignity. However, sustainability remains a primary challenge, requiring long-term institutional commitment and community-based maintenance models. This study contributes to the discourse on how philanthropic interventions can transform the "academic mood" in faith-based educational settings, suggesting that infrastructure is a fundamental psychosocial support system.